Avascular necrosis of lunate bone: Kienbock disease - Bedel, Cihan; Coşkun, Göker; Türkoğlu, Sefa (Journal of Surgery and Medicine, 2018)
Kienbock disease is a rare disorder involving the lunate, one of the carpal bones, and is therefore not generally included in the differential diagnosis of patients presenting to the emergency department with wrist pain. In this case report, we would like to highlight a case of Kienbock disease in a 28-year-old female patient without any medical or traumatic history. Although it is a very rare disease of the lunate, emergency physicians should consider Kienbock disease in those patients with complaints of pain, swelling and limitation of motion of the wrist. An overlooked diagnosis or misdiagnosis may lead to bony ischemia, necrosis, and ultimately collapse of the bone.